Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1177/1523422310394757
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Development and Society: Human Resource Development’s Role in Embedding Corporate Social Responsibility, Sustainability, and Ethics in Organizations

Abstract: Human resource development (HRD) is increasingly expected to play a facilitative role in corporate social responsibility (CSR), sustainability, and ethics in organizations. However, there is also significant skepticism concerning HRD’s ability to make a contribution to these areas. It is criticized for moving away from its mission to advocate humanistic values in organizations to totally embracing a short-term business agenda. This article argues that societal HRD (SHRD) can make an important and long-lasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
205
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(208 citation statements)
references
References 47 publications
(44 reference statements)
1
205
0
2
Order By: Relevance
“…CSR represents an organization's actions and policies that impact not just economic performance, but also performance with respect to social and environmental impact (Aguinis & Glavas 2012). Garavan & McGuire (2010) concluded that there is a pressing need to examine the ways in which knowledge and expertise can be developed for the benefit of individuals, groups, organizations, communities, and humanity as a whole. Many organizations, including IBM, United Parcel Service, PwC, and General Mills, seek to enhance their brands through CSR by providing opportunities for employees to work on projects that help underdeveloped, underserved, and impoverished local and global communities and, at the same time, broaden employees' skill sets (for example, see http://www.community.ups.com/ Community/Community1Internship1Program).…”
Section: Employment Branding and Social Responsibilitymentioning
confidence: 99%
“…CSR represents an organization's actions and policies that impact not just economic performance, but also performance with respect to social and environmental impact (Aguinis & Glavas 2012). Garavan & McGuire (2010) concluded that there is a pressing need to examine the ways in which knowledge and expertise can be developed for the benefit of individuals, groups, organizations, communities, and humanity as a whole. Many organizations, including IBM, United Parcel Service, PwC, and General Mills, seek to enhance their brands through CSR by providing opportunities for employees to work on projects that help underdeveloped, underserved, and impoverished local and global communities and, at the same time, broaden employees' skill sets (for example, see http://www.community.ups.com/ Community/Community1Internship1Program).…”
Section: Employment Branding and Social Responsibilitymentioning
confidence: 99%
“…However, this does not mean that recourse to essentialism and the attribution of particular talents to particular kinds of people (a talent for caring being attributed to women rather than men, for example) is automatically avoided, but the use of the Capability Approach in conceptualising and evaluating talent programmes goes a long way to promoting the kind of vigilance necessary in avoiding these pitfalls. Therefore, sincere efforts by organizations to position talent could reveal how HRD can connect CSR, ethics and sustainability (Ardichvilli, 2013;Garavan and McGuire, 2010) and our contribution to this agenda is to show how inclusive talent management can be conceptualised and contribute to thinking in this field.…”
Section: Sustainabilitymentioning
confidence: 99%
“…This premise is furthered by taking Moon's (2004) view that CSR is based upon social and human interaction with their environments. Garavan and McGuire (2010) go further, suggesting that CSR involves strong organizational commitment to social obligations inherent within employees and that CSR obligations are mobilized by social compulsions. As Marrewijk (2003) declares, employees and organizations are mutually dependent-organizations support their employees, creating value as an agency, and are in constant exchange with its stake holders, thus reflect vertical and horizontal communion.…”
Section: Ecological Systems Theory Approach To Csr 371mentioning
confidence: 97%
“…It is suggested that using the ecological framework for CSR understanding as an analytical tool may allow for a more localized understanding while providing a true stakeholder analysis. This approach reflects the thoughts of Moon (2004) and Garavan and McGuire (2010), where CSR is based upon social and human interactions. And as a result of advanced capitalism, globalization, and an increasing transient workforce, modernity and postmodern society exist in parallel, intertwined within regional and national cultures.…”
Section: Ecological Systems Theory Approach To Csr 379mentioning
confidence: 99%